Do microbial communities in soils of the Bolivian Altiplano change under economic pressures for shorter fallow periods? - Gomez Montaño, Lorena (Kansas State University, 2012)
Traditional fallow periods in the Bolivian highlands are being shortened in an effort to increase short-term crop yields, with potential long-term impacts on soil communities. Using 454-pyrosequencing, we characterized fungal and bacterial community responses to (1) the length of fallow period and (2) the presence of the plants Parasthrephia sp. or Baccharis sp. (both locally known as ‘thola’). Thola is widely considered by farmers as beneficial to soil health, although it is also frequently harvested as a source of fuel by farmers. Soils in one study area, Ancoraimes, had higher levels of organic matter, nitrogen and other macronutrients compared to the other study area, Umala. In our analyses, Ancoraimes soils supported more diverse fungal communities, whereas Umala had more diverse bacterial communities. Unexpectedly, the longer fallow periods were associated with lower fungal diversity in Umala and lower bacterial diversity in Ancoraimes. Fungi assigned to genera Verticillium, Didymella, and Alternaria, and bacteria assigned to genera Paenibacillus, Segetibacter, and Bacillariophyta decreased in abundance with longer fallow period. The presence of thola did not significantly affect overall soil fungal or bacterial diversity, but did increase the frequency of some genera such as Fusarium and Bradyrhizobium. Our results suggest that fallow period has a range of effects on microbial communities, and that the removal of thola from the fields impacts the dynamics of the soil microbial communities.
Keywords: Microbial communities; Fallow period; Bolivia; Altiplano (highland) region; 454-pyrosequencing; Ecology (0329); Microbiology (0410); Plant Pathology (0480)